Psikologi Keluarga Islam sebagai Disiplin Ilmu (Telaah Sejarah dan Konsep) - Ratna Suraiya; Nashrun Jauhari (Nizham Jurnal Studi Keislaman, 2020)
Islamic family psychology is currently being developed by a number of experts in the country, both in Islamic scientific studies and in handling practical Islamic family therapy. However, from the development efforts made, it often appears that the identity of the study is blurred between as an Islamic study and between a study from a Western perspective. The main asset to uncover the obscure curtain in the concept of this study is through tracing the psychological history of the Islamic family, so that it can provide an insight into the epistemological framework and the purpose of its study. The research succeeded in finding several points of findings: (1) Islamic family psychology emerged as a scientific study in the 1980s, after the development of family psychology studies in the 1960s in the West; (2) the emergence of Islamic family psychology studies was triggered by a mission to respond back to the pace of development of family psychology studies in the West which increasingly hegemony in the Islamic world; (3) the concept of Islamic family psychology is based on Islamic teachings which uphold human values, especially in the character of human creation; (4) the psychological dimension of each family person is always touched by Islamic teachings in order to create a Sakinah family.